If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x = 2tanh(x) Multiply ahnt * x x = 2ahntx Solving x = 2ahntx Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2ahntx' to each side of the equation. -2ahntx + x = 2ahntx + -2ahntx Combine like terms: 2ahntx + -2ahntx = 0 -2ahntx + x = 0 Factor out the Greatest Common Factor (GCF), 'x'. x(-2ahnt + 1) = 0Subproblem 1
Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0Subproblem 2
Set the factor '(-2ahnt + 1)' equal to zero and attempt to solve: Simplifying -2ahnt + 1 = 0 Reorder the terms: 1 + -2ahnt = 0 Solving 1 + -2ahnt = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -2ahnt = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -2ahnt = 0 + -1 -2ahnt = 0 + -1 Combine like terms: 0 + -1 = -1 -2ahnt = -1 Add '2ahnt' to each side of the equation. -2ahnt + 2ahnt = -1 + 2ahnt Combine like terms: -2ahnt + 2ahnt = 0 0 = -1 + 2ahnt Simplifying 0 = -1 + 2ahnt The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Solution
x = {0}
| 14m=400.0 | | 10x+12=32 | | x=tanh(x) | | x-4.2=6 | | 12.67(a-3)=.5 | | 1.4y=7 | | -6(4x-3)+5(5x-4)-8=7-8 | | 2(y-2)-4=10 | | 2x^2-5x+245=0 | | -3n+9=-4n+5 | | 3X+4-5X=-10 | | 12x^4+x^2-6=0 | | 60+2x=7(x+60) | | X^2+y^2+Z^2=50 | | -3n+9=-4+5 | | 60+2x=7(x+30) | | 3d+8=2(d+4) | | x+3.5=2.15 | | 14+4p=5p | | -3.8x=51.68 | | 8xy-8y+yx-y= | | 5(x-2)=34 | | y=5sin(5x+20)-2 | | -27x=39.15 | | 8-3x+8=3+4x | | a*3-8=19 | | 28-10x=12+6x | | x-7.2=-4.4 | | -(y+4)=36 | | X+4=4(1-X)+5x | | .65x=25 | | -6t=60+10t |